Dibromocarbene addition to bicyclo[1.1.0]butanes: A facile route to substituted bicyclo[1.1.1]pentanes - Flynn C. Attard; Andrii Slobodianyk; Roman Bychek; Yaroslav Panasiuk; Philipp Neigenfind; Luca Massaro; Michael G. Gardiner; Vadym V. Levterov; Phil S. Baran; Pavel K. Mykhailiuk; Lara R. Malins (Proceedings of the National Academy of Sciences, 2025)
Strained, multicyclic hydrocarbons are increasingly important structural motifs for drug discovery. In particular, substituted bicyclo[1.1.1]pentanes (BCPs) have risen to prominence as bioisosteres for the ubiquitous benzene ring. Despite their favorable pharmacokinetic properties, synthetic strategies toward BCPs suffer from significant drawbacks—namely an overreliance on [1.1.1]propellane, an operationally challenging to utilize starting material which complicates scale-up and hampers widespread adoption of these motifs. In this work, the synthesis of 2,2-dibromo BCPs is described, presenting a class of versatile substituted BCPs and circumventing the need for [1.1.1]propellane-based precursors. Scalable access to these compounds is demonstrated in a simple and inexpensive process, and their applicability for medicinal chemistry campaigns is highlighted through the synthesis of a diverse range of valuable building blocks—including highly sought-after bridge heteroarylated BCP derivatives which are prepared via an electrocatalytic cross-coupling procedure.